Distally based lateral supramalleolar flap for reconstructing distal foot defects in India: a prospective cohort study - Raja Kiran Kumar Goud; Palukuri Lakshmi; Sanujit Pawde; Madhulika Dharmapuri; Swati Sankar; Sandeep Reddy Chintha (Journal of Trauma and Injury)
Purpose Defects involving the ankle and foot are often the result of road traffic accidents. Many such defects are composite and require a flap for coverage, which is a significant challenge for reconstructive surgeons. Various locoregional options, such as reverse sural artery, reverse peroneal artery, peroneus brevis muscle, perforator-based, and fasciocutaneous flaps, have been used, but each flap type has limitations. In this study, we used the distally based lateral supramalleolar flap to reconstruct distal dorsal defects of the foot. The aim of this study was to analyze the efficacy of the flap in reconstructing distal dorsal defects of the foot. The specific objectives were to study the adequacy, reach, and utility of the lateral supramalleolar flap for distal defects of the dorsum of the foot; to observe various complications encountered with the flap; and to study the functional outcomes of reconstruction. Methods The distal dorsal foot defects of 10 patients were reconstructed with distal lateral supramalleolar flaps over a period of 6 months at a tertiary care center, and the results were analyzed. Results We were able to effectively cover distal foot defects in all 10 cases. Flap congestion was observed in two cases, and minor graft loss was seen in two cases. Conclusions The distally based lateral supramalleolar flap is a good pedicled locoregional flap for the coverage of distal dorsal foot and ankle defects of moderate size, with relatively few complications and little morbidity. It can be used as a lifeboat or even substitute for a free flap.